A Simple Route to the Synthesis of Pt Nanobars and the Mechanistic Understanding of Symmetry Reduction. Issue 8 (23rd December 2020) - Chen, Ruhui; Nguyen, Quynh N.; Zhao, Ming; Chen, Zitao; Chi, Miaofang; Xia, Younan
Abstract: Noble‐metal nanocrystals with anisotropic shapes have received increasing interest owing to their unique properties. Here, a facile route to the preparation of Pt nanobars with aspect ratios tunable up to 2.1 was reported by simply reducing a Pt IV precursor in N, N ‐dimethylformamide (DMF) at 160 °C in the presence of poly(vinyl pyrrolidone) (PVP). In addition to its commonly observed roles as a solvent and a reductant, DMF could also decompose to generate CO, a capping agent capable of selectively passivating Pt{100} facets to promote the formation of nanobars. The size and aspect ratio of the nanobars could be tuned by varying the amount of Pt IV precursor involved in the synthesis, as well as the concentration of PVP because of its dual roles as a stabilizer and a co‐reductant. Our mechanistic study indicated that the anisotropic growth resulted from both particle coalescence and localized oxidative etching followed by preferential growth. Abstract : Pt nanobars : A facile route to the preparation of Pt nanobars with aspect ratios tunable up to 2.1 is reported by simply reducing a Pt IV precursor in N, N ‐dimethylformamide at 160 °C in the presence of poly(vinyl pyrrolidone). Our mechanistic study indicates that the anisotropic growth results from both particle coalescence and localized oxidative etching followed by preferential growth.